Investigation of localized delivery of diclofenac sodium from poly(D,L-lactic acid-co-glycolic acid)/ poly(ethylene glycol) scaffolds using an in vitro osteoblast inflammation model - Sidney, Laura E.; Heathman, Thomas R.J.; Britchford, Emily; Abed, Arif Abed; Rahman, Cheryl V.; Buttery, Lee D.K. (Mary Ann Liebert, 2014)
Nonunion fractures and large bone defects are significant targets for osteochondral tissue engineering strategies. A major hurdle in the use of these therapies is the foreign body response of the host. Herein, we report the development of a bone tissue engineering scaffold with the ability to release anti-inflammatory drugs, in the hope of evading this response. Porous, sintered scaffolds composed of poly(D,L-lactic acid-co-glycolic acid) (PLGA) and poly(ethylene glycol) (PEG) were prepared with and without the anti-inflammatory drug diclofenac sodium. Analysis of drug release over time demonstrated a profile suitable for the treatment of acute inflammation with ∼80% of drug released over the first 4 days and a subsequent release of around 0.2% per day. Effect of drug release was monitored using an in vitro osteoblast inflammation model, comprised of mouse primary calvarial osteoblasts stimulated with proinflammatory cytokines interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and interferon-γ (IFN-γ). Levels of inflammation were monitored by cell viability and cellular production of nitric oxide (NO) and prostaglandin E2 (PGE2). The osteoblast inflammation model revealed that proinflammatory cytokine addition to the medium reduced cell viability to 33%, but the release of diclofenac sodium from scaffolds inhibited this effect with a final cell viability of ∼70%. However, releasing diclofenac sodium at high concentrations had a toxic effect on the cells. Proinflammatory cytokine addition led to increased NO and PGE2 production; diclofenac-sodium-releasing scaffolds inhibited NO release by ∼64% and PGE2 production by ∼52%, when the scaffold was loaded with the optimal concentration of drug. These observations demonstrate the potential use of PLGA/PEG scaffolds for localized delivery of anti-inflammatory drugs in bone tissue engineering applications.